Exploring Malaysian university students’ awareness of green computing - Tunku Ahmad, Tunku Badariah; Bello, Abdullahi; Nordin, Mohamad Sahari (Global Science and Technology Forum (GSTF), 2013)
This study explored Malaysian university students’ awareness of green computing in two aspects, i.e. vocabulary and issues, and sought to ascertain whether these two aspects were influenced by gender and field of study (ICT versus non-ICT). A total of 224 university students from ICT- and non-ICT related fields participated in the survey. Students filled out a green computing questionnaire with 21 items measuring awareness of vocabulary and issues. Descriptive statistics, independent-samples t-test and Principal Components Analysis (PCA) were used to analyze the data. Results show that a majority of students lacked awareness of terms, ideas and issues central to green computing, such as E-PEAT, Energy Star, green PC, Malaysia Green Technology Policy, e-waste, and carbon-free computing. The PCA analysis extracted two factors, named Environmental Protection and Nature of Computers, that could be used to explain students’ lack of familiarity with green ICT. Field of study was shown to impact awareness in all the aspects measured in favor of students educated in ICT-related fields, but the findings produced mixed gender effects. The results indicate the need for green computing education to be integrated into higher education curriculum and for university-led green initiatives to be implemented on Malaysian university campuses to increase awareness in the subject matter.